STRATEGI BIMBINGAN KARIR MENGGUNAKAN LAYANAN KLASIKAL UNTUK MENINGKATKAN PEMAHAMAN PERENCANAAN PEMILIHAN SEKOLAH LANJUTAN SISWA SMP : EXPERIMENTAL DESIGN - Kushendar Kushendar (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2019)
Career guidance focuses on life planning, a process of continuous self-development in helping students with career planning. The counselor has a big enough role in helping to provide an understanding of career planning from an early age. One of the services that can be provided by counselors is classical services, which focus on providing information in a systematic and comprehensive manner. The subjects of this study were determined using a purposive sampling technique using the experimental research method of the One-Group Pretest-Posttest design. The data collection instrument used multiple-choice tests. The data obtained were analyzed quantitatively by using the t-test. The results showed that after being given the treatment there was a significant change in the understanding of career planning in class VIII students at SMP Negeri 1 PalembangÂ